2016
DOI: 10.1128/jb.00474-15
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Signal Transduction Systems That Regulate the Temporal and Spatial Expression of Myxococcus xanthus Sporulation Genes

Abstract: bWhen starved for nutrients, Myxococcus xanthus produces a biofilm that contains a mat of rod-shaped cells, known as peripheral rods, and aerial structures called fruiting bodies, which house thousands of dormant and stress-resistant spherical spores. Because rod-shaped cells differentiate into spherical, stress-resistant spores and spore differentiation occurs only in nascent fruiting bodies, many genes and multiple levels of regulation are required. Over the past 2 decades, many regulators of the temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…Previous work indicated that the Nla28 EBP is a response regulator that forms a two component signal transduction system with the membrane-bound histidine kinase sensor Nla28S 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicated that the Nla28 EBP is a response regulator that forms a two component signal transduction system with the membrane-bound histidine kinase sensor Nla28S 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…xanthus NtrC-like RRs are known to regulate such complex behaviors as multicellular fruiting body formation, sporulation, T4P-dependent social motility, and predation [ 3 , 25 , 26 , 29 , 30 , 32 , 33 , 35 , 36 , 55 ]. There is also evidence that there are hierarchal and/or overlapping transcriptional programs mediated by these complex TCS networks [ 3 , 33 ]. Therefore, M .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several NtrC-like RRs and related proteins collectively described as NtrC-like activators (Nla) are known to coordinate development and motility of M . xanthus [ 3 , 25 , 26 , 28 36 ]. Consistent with the paradigm that TCS maintain signaling fidelity at the biochemical level, broad cross-phosphorylation ("cross talk") between these systems does not seem to occur in M .…”
Section: Introductionmentioning
confidence: 99%
“…Two-component systems are widely used by bacteria to sense and respond to their environments [21, 23, 35–40]. Although much work has been done to understand the cellular targets of TCSs, the signals that activate these TCSs remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%